Percutaneous Pedicle Screw for Thoracolumbar Fractures: A Long-term Follow-up - Furtado, Marcos Vinícius da Rocha; Braga, Gabriel Santos; Rossanez, Roberto; Herrero, Carlos Fernando Pereira da Silva (Revista Brasileira de Ortopedia, 2024)
Objective: This is a retrospective cohort study to analyze the long-term outcomes of thoracolumbar spine fracture patients who underwent minimally invasive percutaneous fixation.Methods: The cases of 17 patients with thoracolumbar spine fractures who had percutaneous fixation between 2009 and 2011 were the subject of a retrospective analysis. Clinical and radiographic variables were collected. For the clinical evaluation the questionnaires SF-36 and Oswestry were used. Radiographic parameters were evaluated using fracture's classification based on Magerls's criteria, the fractured vertebra's wedging angle, and the affected segment's segmental Cobb angle. The measures were made at different stages: before surgery, immediately after surgery, one year later, and at a late follow-up (5 years later). Trauma associated injuries, post-surgical and implant related complications were among the additional information taken into account.Results: The SF-36 questionnaire showed averages above 63,5% in all domains in the late postoperative data (from 5 years after the surgery). Oswestry questionnaire answers showed minimal or no physical limitations in 80% of the patients with a mean score of 10,8%±10,5. The average preoperative Cobb angle value was 5,53° ± 13,80° of kyphosis, the immediate postoperative 2,18° ± 13,38° of kyphosis, one year postoperative 5,26 ± 13,95° of kyphosis, and the late follow-up 8,78° ± 15,06° of kyphosis. The mean correction was 3,35°, and mean loss of correction was 6,6°. There were no complications observed, no case of neurological deficit, infection or implant failure occurred.Conclusion: Thoracolumbar vertebrae fractures can be surgically treated with positive late clinical and radiological outcomes and low complication rates using a minimally invasive percutaneous method.
Keywords: minimally invasive surgical procedures; spinal fractures; patient outcome assessment